Tremor in Multiple System Atrophy – a review - Kaindlstorfer, Christine (Columbia University Libraries/Information Services, 2013)
BACKGROUND: Multiple system atrophy (MSA) is a rare neurodegenerative movement disorder characterized by a rapidly progressive course. The clinical presentation can include autonomic failure, parkinsonism, and cerebellar signs. Differentiation from Parkinson’s disease (PD) is difficult if there is levodopa-responsive parkinsonism, rest tremor, lack of cerebellar ataxia, or mild/delayed autonomic failure. Little is known about tremor prevalence and features in MSA. METHODS: We performed a PubMed search to collect the literature on tremor in MSA and considered reports published between 1900 and 2013. RESULTS: Tremor is a common feature among MSA patients. Up to 80% of MSA patients show tremor, and patients with the parkinsonian variant of MSA are more commonly affected. Postural tremor has been documented in about half of the MSA population and is frequently referred to as jerky postural tremor with evidence of minipolymyoclonus on neurophysiological examination. Resting tremor has been reported in about one-third of patients but, in contrast to PD, only 10% show typical parkinsonian “pill-rolling” rest tremor. Some patients exhibit intention tremor associated with cerebellar dysmetria. In general, MSA patients can have more than one tremor type owing to a complex neuropathology that includes both the basal ganglia and pontocerebellar circuits. DISCUSSION: Tremor is not rare in MSA and might be underrecognized. Rest, postural, action and intention tremor can all be present, with jerky tremulous movements of the outstretched hands being the most characteristic. However, reviewing the data on tremor in MSA suggests that not every shaky movement satisfies tremor criteria; therefore, further studies are needed.